2020
DOI: 10.3390/su12052128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feed Concentrate Intake on the Environmental Impact of Dairy Cows in an Alpine Mountain Region Including Soil Carbon Sequestration and Effect on Biodiversity

Abstract: Several studies on the environmental impacts of livestock enterprises are based on the application of life cycle assessments (LCA). In Alpine regions, soil carbon sequestration can play an important role in reducing environmental impacts. However, there is no official methodology to calculate this possible reduction. Biodiversity plays an important role in the Alpine environment and is affected by human activities, such as cattle farming. Our aim was to estimate the carbon footprint (CF) of four different dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…In contrast, dairy LCAs usually presented their functional unit per liter or kg of dairy product (e.g. 115,118,145 ). Alternatively, LCAs for the livestock industry frequently used 'kg of live weight' as functional unit (e.g.…”
Section: Soil Carbon Sequestration (Scs)mentioning
confidence: 99%
“…In contrast, dairy LCAs usually presented their functional unit per liter or kg of dairy product (e.g. 115,118,145 ). Alternatively, LCAs for the livestock industry frequently used 'kg of live weight' as functional unit (e.g.…”
Section: Soil Carbon Sequestration (Scs)mentioning
confidence: 99%
“…Wilkes et al ( 2020 ) observed that in farms with different feeding systems, the amount of kg CO 2 -eq was significantly higher in pure grazing systems than those from zero-grazing to semi-grazing. Therefore, such results would explain the lower value found in our study (in a semi-intensive system) once the pasture-based feed is directly correlated with the intensity of GHG emissions due to enteric fermentation (Sabia et al 2020 ).…”
Section: Resultsmentioning
confidence: 62%
“…Different European studies (e.g. Salvador et al , 2017; Eldesouky et al , 2018; Horrillo et al , 2020; Sabia et al , 2020) indicate that considering the potential of on-farm SOC sequestration could offset the C footprint of sheep and goat milk by up to 90%. In this study, we estimated values of SOC sequestration potential for current small ruminant systems in Europe that could offset about 17–23% of the C footprint, depending on the assumptions chosen.…”
Section: Discussionmentioning
confidence: 99%